Pancreaticobiliary Maljunction and Congenital Biliary Dilatation (Springer Singapore, 2018)
From embryology to epidemiology, pathophysiology, diagnosis, complications, treatment and prognosis, this book provides a comprehensive overview and the latest evidence-based data on pancreaticobiliary maljunction (PBM), a congenital malformation in which the pancreatic and bile ducts join anatomically outside the duodenal wall. Resulting in various pathologic conditions, such as biliary cancer and pancreatitis, immediate prophylactic surgery is recommended upon diagnosis. The standard operative procedure for congenital biliary dilatation (CBD) is extrahepatic bile duct resection with bilioenteric anastomosis, but the optimal treatment of adult patients with PBM without biliary dilatation remains highly debatable. This book, written by pioneering editors and authors provides latest data, sheds new light on the disease. With abundant figures to aid understanding, Pancreaticobiliary Maljunction and Congenital Biliary Dilatation appeals to a wide readership, especially adult and pediatric surgeons, physicians including gastroenterologists and endoscopists, as well as radiologists and pathologists.